Potential cytotoxic effect of chronic administration of creatine, a nutrition supplement to augment athletic performance - Yu, P. H.; Deng, Y. (Medical Hypotheses, 2000)
Creatine is alleged to be an ergogenic aid to enhance sports performance and recently became a popular sports nutrition supplement. Although short-term supplementation of creatine has not been associated with major health risks, the safety of prolonged use has caused some concern. The present study demonstrates that creatine is metabolized to methylamine, which is further converted to formaldehyde by semicarbazide-sensitive amine oxidase (SSAO). Formaldehyde is well known to cross-link proteins and DNAs, and known to be a major environmental risk factor. SSAO-mediated production of toxic aldehydes has been recently proposed to be related to pathological conditions such as vascular damage, diabetic complications, nephropathy, etc. Chronic administration of a large quantity of creatine can increase the production of formaldehyde, which may potentially cause serious unwanted side-effects. Med Hypotheses 2000 May;54(5):726-8